Numerical Study for Performance Evaluation of Plastic Solar Air Heater with Different Cross-Sectional Configuration - Ayman Bakry; Yaser El-Samadony; S. Elsayed; E. Ebied (Journal of Engineering Research - Egypt)
In this research, a numerical investigation was performed on five solar air heaters with different cross-sectional shape to find the best configuration relevant to thermal performance. The selected tested shapes in this study were (circular, semi-circular, half-circle plus isosceles triangle, half circle-negative isosceles triangle shape and crescent shape) and all tested shapes hade the same absorber surface area. The effect of two parameter (velocity and solar radiation intensity) on thermal performance of solar air heater were studied numerically by ANSYS 14.0. The velocity of air was changed from 0.25 to 2.0 (m.s -1 ). Results indicated that the highest efficiencies were accomplished for the circular configuration and reached to about 51.79% at solar radiation intensity 850 (W.m-2 ). The solar radiation intensity was changed from 400 to 1200 (W.m-2 ). Results indicated that the highest efficiencies were accomplished for the circular configuration and reached to about 35.51% at air velocity 1.0 (m.s-1 ).